2022
DOI: 10.1017/s0033291722002100
|View full text |Cite
|
Sign up to set email alerts
|

Variables influencing conditioning-evoked hallucinations: overview and future applications

Abstract: Hallucinations occur in the absence of sensory stimulation and result in vivid perceptual experiences of nonexistent events that manifest across a range of sensory modalities. Approaches from the field of experimental and cognitive psychology have leveraged the idea that associative learning experiences can evoke conditioning-induced hallucinations in both animals and humans. In this review, we describe classical and contemporary findings and highlight the variables eliciting these experiences. We also provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…These limitations aside, our data extend the findings of previous studies, which have leveraged mediated learning procedures as a tool for examining reality testing in animal models of schizophrenia (see Fry et al, 2022, for an extensive discussion). We know that animals that receive neonatal ventral hippocampal lesions (McDannald et al, 2011), chronic administration of N-methyl-D-aspartate receptor antagonists (Koh et al, 2018; Wu et al, 2020), phospholipase C ß1 knockdown (Kim & Koh, 2016), or transgenic expression of DISC-1 (Fry et al, 2020) have been shown to display enhanced susceptibility to impaired reality testing.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…These limitations aside, our data extend the findings of previous studies, which have leveraged mediated learning procedures as a tool for examining reality testing in animal models of schizophrenia (see Fry et al, 2022, for an extensive discussion). We know that animals that receive neonatal ventral hippocampal lesions (McDannald et al, 2011), chronic administration of N-methyl-D-aspartate receptor antagonists (Koh et al, 2018; Wu et al, 2020), phospholipase C ß1 knockdown (Kim & Koh, 2016), or transgenic expression of DISC-1 (Fry et al, 2020) have been shown to display enhanced susceptibility to impaired reality testing.…”
Section: Methodssupporting
confidence: 80%
“…Further, we show that inactivation of this circuit is sufficient to yield impaired reality testing in wild-type mice, adding yet more evidence to point toward insular dysfunction as an area of interest for researchers looking to explore novel drug targets for treatment in schizophrenia. These studies add to a small but growing body of literature attempting to investigate the neurobiology of positive symptomology in animal models (Fry et al, 2022) as well as further our understanding of the neurobiological impacts following perturbations of the DISC-1 genetic locus. Future work with a continued focus on revealing circuit-specific pathways to impaired reality testing in animal models will be invaluable as we strive toward the ultimate goal of improving treatment modalities for humans with schizophrenia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, given our approach intersects appetition and aversion, it is possible that we are engaging a heterogeneous population of dopamine cells that include those that respond to high intensity sensory stimuli and are aversive when stimulated 59 . In addition to uncovering novel mechanisms of dopamine action in learning, our studies are relevant to neuropsychiatric endophenotypes of reality testing 60 , and could be leveraged as a tool to attenuate ingestive behavior 61 and substance abuse 62 through dampening, via mesencephalic DA manipulations, the memories associated with reward.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of conditioned hallucinations and mediated conditioning, at least when involving a palatable food as an absent event, is also transient in that the effect is better obtained with a limited rather than an extended amount of training (e.g., Holland, 1998, 2005, Holland et al, 2008. Importantly, the enhanced processing of absent food in the animal models of schizophrenia is often observed in the form of its maintenance in the animal models and its reduction in control animals during extended training (e.g., Busquets-Garcia et al, 2017;Fry et al, 2020Fry et al, , 2022Kim & Koh, 2016; see also Kim & Koh, 2021, for a corresponding pattern of changes in neural activations).…”
Section: Transient Nature Of Sensory Representation and Its Maintenan...mentioning
confidence: 99%